2019
DOI: 10.1098/rspb.2019.1718
|View full text |Cite
|
Sign up to set email alerts
|

Increases and decreases in marine disease reports in an era of global change

Abstract: Outbreaks of marine infectious diseases have caused widespread mass mortalities, but the lack of baseline data has precluded evaluating whether disease is increasing or decreasing in the ocean. We use an established literature proxy method from Ward and Lafferty (Ward and Lafferty 2004 PLoS Biology 2 , e120 ( doi:10.1371/journal.pbio.0020120 )) to analyse a 44-year global record of normalized disease reports from 1970 to 2013. Major marine hosts are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 46 publications
(82 reference statements)
0
61
0
Order By: Relevance
“…The temporal rapidity and geographic heterogeneity of the 2013 sea star wasting disease outbreak made it difficult to narrow down the range of factors, causes, and mechanisms involved at the time. Similar to other multitaxon pandemics (e.g., “white nose” syndrome in bats, chytrid fungi for amphibians, morbillivirus in dolphins) SSWD was elusive in the early stages of study (Hewson et al, 2018; Miner et al, 2018), which is a concern as mass mortalities are increasing in frequency with global change in some taxa (Fey et al, 2015; Tracy, Pielmeier, Yoshioka, Heron, & Harvell, 2019) and require more rapid assessment. Given the central role of asteroid predators in community ecology (Gravem & Morgan, 2017; Menge, 1983; Paine, 1974), as the focal organisms in the 2013 wasting pandemic, and wasting's intermittent recurrence (albeit with different intensity and taxonomic breadth) we desperately need to better understand risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal rapidity and geographic heterogeneity of the 2013 sea star wasting disease outbreak made it difficult to narrow down the range of factors, causes, and mechanisms involved at the time. Similar to other multitaxon pandemics (e.g., “white nose” syndrome in bats, chytrid fungi for amphibians, morbillivirus in dolphins) SSWD was elusive in the early stages of study (Hewson et al, 2018; Miner et al, 2018), which is a concern as mass mortalities are increasing in frequency with global change in some taxa (Fey et al, 2015; Tracy, Pielmeier, Yoshioka, Heron, & Harvell, 2019) and require more rapid assessment. Given the central role of asteroid predators in community ecology (Gravem & Morgan, 2017; Menge, 1983; Paine, 1974), as the focal organisms in the 2013 wasting pandemic, and wasting's intermittent recurrence (albeit with different intensity and taxonomic breadth) we desperately need to better understand risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in them being classed as threatened (US Endangered Species Act; ESA), and critically endangered (IUCN). The primary cause of this decline is disease [2][3][4] and this is particularly worrying for these species as climate change and anthropogenic stressors are now being implicated in increasing disease prevalence, frequency, and severity [5][6][7][8][9][10]. While these two species are now being heavily used in restoration activities in the Caribbean, their disease susceptibility requires a more thorough understanding of the disease dynamics within the remnant populations.…”
Section: Introductionmentioning
confidence: 99%
“…Samples from these genotypes clustered with the year they were exposed to disease, indicating that genotype susceptibility was probably not the cause for the differences in disease prevalence (Fig 2, A). Our results indicate that other factors such as disease type, disease virulence, and the base health of the coral could be potential factors that led to the higher incidence of observed diseases in 2017 [10,26,47]. Additionally, we identified that the A. palmata genes driving the difference between 2016 and 2017 were putative coral ribosomal proteins (Fig 3A, Supp 1).…”
Section: Discussionmentioning
confidence: 78%
“…This has been especially notable for Acropora palmata and Acropora cervicornis , which have seen an 80% reduction throughout their geographic range [2] resulting in them being classed threatened (US Endangered Species Act; ESA), and critically endangered (IUCN). The primary driver of this decline is disease [2–4] and this is particularly worrying for these species as climate change and anthropogenic stressors are now being implicated in increasing disease prevalence, frequency, and severity [510]. These two species are being heavily focused on for restoration activities in the Caribbean, but are historically susceptible to disease, thus it is imperative we understand the disease dynamics within the remnant populations.…”
Section: Introductionmentioning
confidence: 99%